Spatio-temporal patterns of health service delivery and access to maternal, child, and outpatient healthcare in Volta region, Ghana: a repeated cross-sectional ecological study using health facility data - Winfred Dotse-Gborgbortsi; Kristine Nilsen; Ortis Yankey; Anthony Ofosu; Thomas Ankomah; Eric Tweneboah; Ignatius Aklikpe; Chrysantus Kubio; Alberta Biritwum-Nyarko; Andrew Tatem; Jim Wright (Global Health Action)
Background To attain universal health care, health managers need to monitor progress in service uptake, changes and geographic coverage. Although routine health management information systems are now well established in many resource-constrained countries, such data have not yet been used to examine geographic access trends over time. Objective This study aims to quantify changing patterns of geographic access to healthcare in the Volta Region, Ghana. Methods The repeated cross-sectional ecological spatio-temporal analysis used routine health management information systems data from 2016 to 2022, and geospatial data to examine changes in healthcare accessibility and services provided for population subgroups. Changes in healthcare provision, travel time to services and population coverage were estimated. Results Most health facilities (60.6%) provided the same range of services or added new services between 2016 and 2022. Childhood immunisation services had the highest geographic coverage within 30 min of the nearest health facility from 2016 to 2022 (minimum 97.2%), while Caesarean births had the lowest (maximum 75.2%). More health facilities provide antenatal services (2022: 59.9%) than birthing care (2022: 52.6%). Of all new health facilities, 93.2% were Community Health Planning and Services (CHPS) facilities. The majority of the population lived within 30 min of services in 2016 and 2022 for all the services studied. Conclusion The study provides a new approach to monitoring service changes through routine health data and spatial analysis. The analysis provided evidence to improve geographic accessibility, address gaps in service changes and consolidate the gains of high geographic coverage with quality care.